6n-36=n+9

Simple and best practice solution for 6n-36=n+9 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6n-36=n+9 equation:


Simplifying
6n + -36 = n + 9

Reorder the terms:
-36 + 6n = n + 9

Reorder the terms:
-36 + 6n = 9 + n

Solving
-36 + 6n = 9 + n

Solving for variable 'n'.

Move all terms containing n to the left, all other terms to the right.

Add '-1n' to each side of the equation.
-36 + 6n + -1n = 9 + n + -1n

Combine like terms: 6n + -1n = 5n
-36 + 5n = 9 + n + -1n

Combine like terms: n + -1n = 0
-36 + 5n = 9 + 0
-36 + 5n = 9

Add '36' to each side of the equation.
-36 + 36 + 5n = 9 + 36

Combine like terms: -36 + 36 = 0
0 + 5n = 9 + 36
5n = 9 + 36

Combine like terms: 9 + 36 = 45
5n = 45

Divide each side by '5'.
n = 9

Simplifying
n = 9

See similar equations:

| 3(y+3)-2(y-1)=0 | | x+9=-3*2 | | 23=16+7q | | 23=16+7a | | 2.2x-7-1.6x=0.6x-7 | | 2(x+4)=3x-1*5 | | 7g-1=13-5g | | n-6=2-3n | | -4y+8(7y-2)=5-4(-4-y) | | Y-44=-27 | | x+4=20x | | x+4=10x | | 2a(a-5)+4(a-5)=a | | 101(3a-1)=149 | | 7(x+20)=x+2 | | D-6=-9 | | -5(3p+3)= | | 0=x^2-5x-5 | | (8x+9)(3x-4)=0 | | (x+7)*.05+.4=.1x | | y=x^2-5x-5 | | 5(16-n)+100n=1125 | | 2x=m | | 2x-8x+5x-4x= | | 4n-3n-7=44 | | -2(x+5)=2(x-1) | | -2(4-3)=6 | | 100-80= | | 4n-3n-7=54 | | 0.4x-0.5(2x+7)=0.7(x+3) | | 2+35324= | | -66=-11g+33 |

Equations solver categories